Vaginal Microecology Disturbance and Immune Dysregulation Are Associated with Human Papillomavirus Infection: Insights from a Two-year Study of Vaginal Microecology - Sheng Q; Cui X; Zhang J; Yang F; Zeng L (International Journal of General Medicine)
Qunying Sheng,1 Xiaojie Cui,1 Junneng Zhang,2 Fang Yang,1 Lingqian Zeng1 1Department of Gynecology, the Fifth Hospital of Xiamen, Xiamen, Fujian, 361101, People’s Republic of China; 2Department of Clinical Laboratory, the Fifth Hospital of Xiamen, Xiamen, Fujian, 361101, People’s Republic of ChinaCorrespondence: Lingqian Zeng, Department of Gynecology, the Fifth Hospital of Xiamen, Xiamen, Fujian, 361101, People’s Republic of China, Tel +86-18050723339, Email wujungai123@hotmail.comBackground: Human papillomavirus (HPV) infection is essential for cervical cancer (CC) development, yet only a fraction of infections persist and progress. Vaginal microecology and immune responses may play pivotal roles in determining HPV outcomes. This study aimed to explore the association between vaginal microecological alterations, immune-inflammatory markers, and the natural course of HPV infection.Methods: We retrospectively analyzed 312 women undergoing HPV genotyping, vaginal microecological evaluation, and cytokine profiling over a two-year period. Logistic regression and ROC curve analyses were used to identify predictors of HPV persistence or clearance.Results: HPV-positive women exhibited significantly higher rates of elevated vaginal pH (76.2%), bacterial vaginosis (37.1%), reduced hydrogen peroxide production (41.0%), sialidase activity (33.3%), and Community state type IV (CST IV) dominance (34.3%) compared to HPV-negative women (P< 0.001). Multivariate analysis revealed elevated pH, Nugent score ≥ 7, negative H2O2 production, CST IV, biofilm formation, and high IL-6 levels as independent predictors of HPV persistence. ROC analysis showed the combined predictive model achieved an AUC of 0.842. Kaplan–Meier survival analysis indicated that women with normal vaginal microecology had significantly higher HPV clearance rates at 24 months (90.1%) compared to those with dysbiosis (66.2%, P< 0.001). Additionally, persistent infections were associated with elevated TNF-α, reduced IL-12, higher CRP, and oxidative stress markers.Conclusion: Vaginal microecological imbalance and immune dysregulation are major determinants of HPV persistence. Comprehensive assessment of these factors may improve risk stratification and guide individualized interventions for HPV-infected women.Keywords: epidemiology, inflammation, human papillomavirus, receiver operator curve, vaginal microecology